La scrittura della decolonizzazione: José María Arguedas - Giordano, Roberta (Studia Europaea Gnesnensia, 2011)
This paper is aimed at analysing the mechanism of choosing the literary language in some writings of José María Arguedas. The author made this choice according to several perspectives: cultural, political and emotional.